Microwave Plasma Enhancing Mg-Based Hydrogen Storage: Thermodynamics Evaluation and Economic Analysis of Coupling SOFC for Heat and Power Generation - Wang, Huan; Yan, Hongli; Ren, Jianwei; Li, Bo; Nyallang Nyamsi, Serge; Wu, Zhen (Frontiers in Thermal Engineering, 2022)
Graphical Abstract